Sleep Disturbance is Associated With Higher Plasma Aβ Levels in Cognitively Normal Adults—A Population-Based Cross-Sectional Study - Gao, Yao; Wei, Shan; Gao, Fan; Gao, Ling; Dang, Liangjun; Shang, Suhang; Chen, Chen; Huo, Kang; Wang, Jingyi; Wang, Jin; Qu, Qiumin (Frontiers in Aging Neuroscience, 2021)
Objective: Growing evidence suggests that sleep disturbance is a risk factor for Alzheimer's disease (AD). Amyloid-β (Aβ) deposition in the brain is a main pathophysiology of AD. Considering that peripheral Aβ level is associated with brain Aβ deposition, the present study investigated the relationship between sleep disturbance and plasma Aβ levels. Methods: This is a population-based cross-sectional study. A total of 1,459 participants from a village in the suburbs of Xi'an, China, were enrolled from January 3, 2017 to March 26, 2017. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and a PSQI score of <5 points was considered as good sleep quality and a PSQI score of >10 points as poor sleep quality. Cognitive function was assessed with the Mini-Mental State Examination (MMSE). Fasting venous blood was taken in the morning, and the plasma Aβ levels were measured using ELISA. The relationships between plasma Aβ levels and sleep quality were analyzed using multiple linear regression. Results: Among the participants, 231 had poor sleep quality (15.83%). The log-transformed Aβ40 level had significant differences among the different sleep groups (F = 3.216, p = 0.040). The log-transformed Aβ40 level was higher in the poor sleep quality group than that in the general sleep quality group [87.17 (73.42, 107.34) vs. 89.69 (74.81, 125.79) pg/ml, p = 0.016]. In bivariate analysis, sleep quality was negatively associated with the log-transformed plasma Aβ40 level (β = −0.025, p = 0.011). Conclusion: In the community population, poorer sleep quality is associated with a higher plasma Aβ40 level. This indicated that sleep disturbance might also involve in dysfunction of peripheral Aβ clearance.